2016
DOI: 10.1016/j.neurobiolaging.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic neurogenesis persists in the aging brain and is controlled by energy-sensing IGF-I pathway

Abstract: International audienceHypothalamic tanycytes are specialized glial cells lining the third ventricle. They are recently identified as adult stem and/or progenitor cells, able to self-renew and give rise to new neurons postnatally. However, the long-term neurogenic potential of tanycytes and the pathways regulating lifelong cell replacement in the adult hypothalamus are largely unexplored. Using inducible nestin-CreERT2 for conditional mutagenesis, we performed lineage tracing of adult hypothalamic stem and/or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 28 publications
2
70
0
Order By: Relevance
“…Contrasting studies have suggested that subpopulations of tanycytes constitute the source (6366). This in itself, however, is controversial as both α- and β-tanycytes have been identified as the possible neurogenic niche, as well as a possible role for insulin-like growth factor (63, 65, 67). Interestingly, in one study, exposure of mice to a high fat diet depleted numbers of putative hypothalamic stem cells, which was associated with impaired glucose tolerance and subsequent obesity (68).…”
Section: Hypothalamic Tanycytes As a Stem Cell Nichementioning
confidence: 99%
“…Contrasting studies have suggested that subpopulations of tanycytes constitute the source (6366). This in itself, however, is controversial as both α- and β-tanycytes have been identified as the possible neurogenic niche, as well as a possible role for insulin-like growth factor (63, 65, 67). Interestingly, in one study, exposure of mice to a high fat diet depleted numbers of putative hypothalamic stem cells, which was associated with impaired glucose tolerance and subsequent obesity (68).…”
Section: Hypothalamic Tanycytes As a Stem Cell Nichementioning
confidence: 99%
“…Studies in transgenic mice harboring mutations along the insulin/IGF-I cascade have revealed a major role for this pathway in NSC exit from quiescence ( Figure 2B) and in premature exhaustion [8,[50][51][52]. Accordingly, mice deficient in FOXO (which is inhibited by insulin signaling), or lacking its transcriptional target and cell cycle inhibitor p21, both display NSC hyperproliferation in vitro and premature exhaustion in vivo [8,50].…”
Section: Insulin/insulin-like Growth Factor Signaling Insulin and Insmentioning
confidence: 99%
“…Accordingly, mice deficient in FOXO (which is inhibited by insulin signaling), or lacking its transcriptional target and cell cycle inhibitor p21, both display NSC hyperproliferation in vitro and premature exhaustion in vivo [8,50]. Conversely, ablation of IGF-I signals in NSCs has been shown to delay age-related decline of adult neurogenesis in olfactory bulb [51] and to enhance [ 1 8 _ T D $ D I F F ] /-tanycyte self-renewal in the hypothalamus of aged mice, preserving this stem cell-like population from age-related attrition [52]. These beneficial effects are reminiscent of neurogenesis rejuvenation by periodic fasting [53] and likely reflect the long-term preservation of the quiescent NSC pool.…”
Section: Insulin/insulin-like Growth Factor Signaling Insulin and Insmentioning
confidence: 99%
See 1 more Smart Citation
“…They also express the molecular machinery that permits glucose sensing (García et al, 2003; Cortés-Campos et al, 2011; Orellana et al, 2012) and transmit signals to AN neurons (Elizondo-Vega et al, 2016). Due to their privileged position in the hypothalamus, tanycytes can also detect mitogenic and neurodifferentiating signals present in the peripheral blood or in the CSF (Robins et al, 2013; Chaker et al, 2016). …”
Section: Hypothalamus and Energy Balancementioning
confidence: 99%